2014
DOI: 10.1038/cddis.2014.398
|View full text |Cite
|
Sign up to set email alerts
|

The activation of G protein-coupled receptor 30 (GPR30) inhibits proliferation of estrogen receptor-negative breast cancer cells in vitro and in vivo

Abstract: There is an urgent clinical need for safe and effective treatment agents and therapy targets for estrogen receptor negative (ER−) breast cancer. G protein-coupled receptor 30 (GPR30), which mediates non-genomic signaling of estrogen to regulate cell growth, is highly expressed in ER− breast cancer cells. We here showed that activation of GPR30 by the receptor-specific agonist G-1 inhibited the growth of ER− breast cancer cells in vitro. Treatment of ER− breast cancer cells with G-1 resulted in G2/M-phase arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 54 publications
8
119
1
3
Order By: Relevance
“…4A). In line with the previous studies [26-28], the dose of 1μM G-1 was selected for further in vitro studies. Furthermore, we conducted knockdown assays in MDA-MB-231 cells to assess whether the inhibitory effects of G-1 depended on GPER activation.…”
Section: Resultsmentioning
confidence: 99%
“…4A). In line with the previous studies [26-28], the dose of 1μM G-1 was selected for further in vitro studies. Furthermore, we conducted knockdown assays in MDA-MB-231 cells to assess whether the inhibitory effects of G-1 depended on GPER activation.…”
Section: Resultsmentioning
confidence: 99%
“…GPER mediates the activation of a network of transduction pathways; however, the actual role elicited by GPER in tumorigenesis is still controversial. Previous studies have shown that GPER may induce cell cycle arrest and inhibition of cancer cell growth (13)(14)(15)(16). Nevertheless, other in vitro and in vivo studies have revealed that GPER triggers cancer cell migration and proliferation (5,17).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that G-1 improves the cognitive abilities and social learning of mice [24,25]. It may also possess anxiolytic potential in mice [26,27]; and potential antineoplasic effects, as it is capable of inhibiting the proliferation of cervical, adrenocortical carcinoma and breast tumor cells [28][29][30]. G-1 has also anti-inflammatory properties, raising T regulatory cell population and IL-10 secretion [31,32].…”
Section: Nanocarriers Effects On the Intracellular Delivery Of Fitc Imentioning
confidence: 99%